2019
DOI: 10.1186/s12864-019-5650-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective translational usage of TSS and core promoters revealed by translatome sequencing

Abstract: Background In mammals, fine-tuned regulation of gene expression leads to transcription initiation from diverse transcription start sites (TSSs) and multiple core promoters. Although polysome association is a critical step in translation, whether polysome selectively uses TSSs and core promoters and how this could impact translation remains elusive. Results In this study, we used CAGE followed by deep sequencing to globally profile the transcript 5′ isoforms in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, although previous studies have reported the translational impact of transcripts isoforms derived from multiple closely situated promoters, 19 , 25 , 26 , 27 , 28 , 29 minor TSSs (alternative TSS selection within the same cluster) have been considered as nonadaptive and the product of molecular errors. 30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although previous studies have reported the translational impact of transcripts isoforms derived from multiple closely situated promoters, 19 , 25 , 26 , 27 , 28 , 29 minor TSSs (alternative TSS selection within the same cluster) have been considered as nonadaptive and the product of molecular errors. 30 …”
Section: Introductionmentioning
confidence: 99%
“…This highlights a potential relevance in gene expression regulation. After all, a differential TSS selection will change the overall length of the mRNA 5' UTR, likely altering the presence of regulatory elements such as upstream open reading frames (uORF); upstream start codons (uAUG); RNA secondary structures; and internal ribosomal entries sites 19-24 . However, although previous studies have reported the translational impact of transcripts isoforms derived from multiple closely situated promoters 19,[25][26][27][28][29] , minor TSSs (alternative TSS selection within the same cluster) have been considered as nonadaptive and the product of molecular errors 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, CAGE was originally used to construct a precise map of transcription start sites (TSSs) and elucidate the "promoteromes" of mammalian cells and tissues. In one analysis involving the tagging of m7G caps on mRNAs, nearly 25% of mammalian m7G caps were not located at already known TSS (14,15). Whole-transcriptome network analyses via technologies such as CAGE might enable a much more comprehensive understanding of the divergence of promoteromes in the precursors of malignancies such as pancreatic cancer (16).…”
Section: Introductionmentioning
confidence: 99%